Pelatihan Gaya Belajar Pada Siswa Kelas 12 TSM 1 SMK Muhammadiyah 2 Ngawi - Roby, Muhammad; Ruhaena, Lisnawati; Kholila, Annisa; Abror, Kholif Miftakhul; Aini, Farida Nur (Abdi Psikonomi, 2024)
Understanding learning styles is important for students. Students will be able to absorb lessons well if they adjust to their learning styles. Therefore, students need to understand their learning styles to improve their learning outcomes. Learning style training can be done to improve students' understanding of learning styles. The training method was chosen as an intervention because it is designed to help students understand the most effective way of learning according to their individual tendencies. Through this training, students are given space to explore learning styles that suit their conditions, whether visual, auditory, or kinesthetic learning styles. After understanding learning styles, students are expected to be able to increase learning effectiveness, maximize their potential, and be more confident in facing learning challenges. Data collection techniques used in this training include questionnaires, interviews, learning style classification instruments, and Pre-Tests and Post-Tests. The results of the training showed an increase in knowledge and understanding of learning styles in grade 12 TSM 1 students.